Helmet use in winter sport activities - attitude and opinion of neurosurgeons and non-traumatic-brain-injury-educated persons - Jung, Carla Sabine; Zweckberger, Klaus; Schick, Uta; Unterberg, Andreas (Acta neurochirurgica, 2011)
Purpose: During the last winter season, some fatal sport injuries with severe traumatic brain injury (TBI) prompted major discussions about protective helmet use. Although ski helmets reportedly lead to a 60% decrease of risk to incur TBI, little is known about the distribution of helmet users and which factors are crucial for the decision to wear a helmet. Especially, it is unknown whether knowledge or experience concerning TBI in winter sports influences the use of helmets, as well as the attitude and opinion of people. Methods: Since treatment of TBI is a major field in neurosurgery, 55 neurosurgical departments (NS) in Germany, Switzerland and Austria were addressed and asked to answer anonymous questionnaires. A “non-trauma-educated” control cohort (NTP) was interviewed in ski resorts in Austria as well as sports equipment stores in Germany. Results: Questionnaires were returned by 465 NS and 546 NTP. Half of NS and NTP wore helmets in winter sports. Although some interviewees showed cognitive dissonant behaviour, experience in TBI after ski or snowboard accidents significantly affected the decision to wear helmets. After the fatal ski accidents, and increased media coverage 15.4% NS and 13.2% NTP bought their helmet. Furthermore, incidence of helmet use in children was correlated with the actual use and disposition of their parents to make the use of helmet compulsory. Conclusions: This study indicates that brain-trauma education affects ones attitude and opinion concerning protective helmet use in winter sports. However, without neglecting educational measures, emotional arguments should be added in the promotion of helmets to make them a popular integral part of winter sport outfits.